Association of the APOEgene polymorphism with diabetic nephropathy - Hasan, Taner; Josifovska, Slavica; Trajkovska, Ivana; Doneva, Daniela; Nedeska, Natasha; Volkanovska Ilijevska, Cvetanka (Bioscientifica, 2020)
The protein isoformes that are products of the Apolipoprotein E (APOB) gene polymorphism have partially altered biological activity and that may lead to greater susceptibility of the patientsto microvascular complications including Diabetic nephropathy (DN)in patients with the Type 2 diabetes mellitus (T2DM). The aim of this study was to evaluate the association between the allele ε2, ε3, and ε4 of the APOE gene, as well as their combination, with the development of DN in patients with T2DM from the North Macedonia. The genotypic and allele frequency of the polymorphisms rs429358 and rs7412 in the APOE gene was determined in a group of patients with T2DM (with and without DN), and in the control group healthy subjects. The study is designed as a case-control genetic association study. The samples from 88 patients with T2DM were analyzed, including 57 patients with DN and 31 without DN and 26 healthy controls. The demographic, clinical and laboratory data were analyzed in addition to the genetic profiling of the patients. Genotyping of the APOE gene polymorphism resulted in determination of the patient’s genotype: ε2/ε2, ε3/ε3, ε4/ε4, ε2/ε3, ε2/ε4 or ε3/ε4, as well as of the alleles: ε2, ε3 or ε4. The results revealed a statistically significant association of the genotype ε2/ε3 (P = 0.016) and the allele ε2 (P = 0.020) with the occurrence of DN compared to the other genotypes and alleles. The presence of this genotype increases the chances of DN by 4,24 folds and the relative risk by 1,50 folds. In conclusion, the correlation of the APOEgene polymorphism and the development of the DN in patients with T2DM was confirmed indicating that there is a potential applicable value in the prognosis and treatment selection.
Keywords: APOB; polymorphisms; Type 2 Diabetes mellitus; Diabetic nephropathy